A descriptive study of benign vocal cord lesions - Bhadesia, Bhoomi; Sorathiya, Rashmi; Joshi, Hetal; Desai, Nisarg; Hirani, Narendra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Various vocal cord lesions have a significant influence on vocalization. In India and other developing countries, the prevailing lower economic status, poor general health of population, different food habits, vocal habits, smoking and drinking habits, unhealthy environment and different social customs definitely influence the incidence of various vocal cord lesions. Objective of this was study was to find out the incidence of various vocal cord lesions, factors affecting the voice and treatment. Methods: This is a prospective study carried out in ENT Department from June 2018 to September 2019 at a tertiary care teaching hospital of Western Gujarat. We evaluated 48 patients who had various lesions on vocal cord. Incidence, age, gender, occupational factors, contributing factors, clinical features, histopathological findings were studied. Results: Vocal cord lesions were more common in males (64.58%), 21 to 40 years of age group. Change of voice (100%) was the most common presenting symptom. Vocal abuse (83.33%) was most common etiological factor. Students (27.08%) were most commonly affected. Maximum cases were of vocal cord nodules (39.58%). All vocal cord lesions (except papilloma) had good recovery with no recurrence. Conclusions: Vocal cord lesions were more common in males and in 3rd and 4th decades of life. Change of voice was the most common presenting symptom. Vocal abuse was most common etiological factor. Students were more affected in vocal cord lesions. Vocal cord nodules were the most common lesions. Microlaryngeal surgery, voice rest and speech therapy are the mainstay of the treatment for benign lesions.